Student Numeracy Ability in Solving Problems on Geometry and Measurement Material - Saffrina Saffrina; Baidullah Baidullah (Publikasi Indonesia, 2024)
Numeracy is the ability to apply number concepts and arithmetic operation skills in daily life, professional development, and the development of science and technology. Numeracy skills play an essential role in the application of number concepts and arithmetic operations in the context of everyday life. This research aims to determine the numeracy skills of class VIII-B students at SMP Negeri 1 Blangpidie in solving problems on geometry and measurement material. The data collection methods used were tests and interviews. From the research results, of the total 27 students involved, 22 students showed very high numeracy skills, reaching a percentage of 81%. Meanwhile, five other students have a high level of numeracy ability, with a percentage of 19%. The level of numeracy ability of class VIII-B students is assessed based on student indicators in solving problems on geometry and measurement material. It can concluded that the numeracy skills of class VIII-B students in solving geometry and measurement material problems have perfect numeracy scores.